1998
DOI: 10.1038/sj.gt.3300746
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coexpression and secretion of anti-atherogenic human apolipoprotein AI and lecithin-cholesterol acyltransferase by cultured muscle cells using adeno-associated virus plasmid vectors

Abstract: Plasma apolipoprotein AI (apoAI) and lecithin-cholesterolThe secretion of apoAI or LCAT by transduced cultures acyltransferase (LCAT) play important roles in reverse was two-to five-fold higher using AAV-based plasmid veccholesterol transport, promoting the removal of excess tors than conventional plasmid vectors. Additionally, cells cholesterol from peripheral cells and reducing formation of transfected with a bicistronic AAV-based vector containing atherosclerotic lesions. Gene augmentation of either apoAI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…29,[31][32][33][34][35] We have examined the feasibility of targeting muscle as a platform for the secretion of anti-atherogenic proteins by the transfection of mouse myoblast cultures with rAAV-based plasmid vectors containing apoA1 and LCAT cDNAs. 42 A significant improvement in secretion of apoA1 and LCAT and retention of vector sequences by transfected cells was observed using the rAAV-based vectors compared with conventional plasmid expression vectors. We also demonstrated that cultured mouse C2C12 cells transfected with a plasmid expression vector containing the CMV promoter driving expression of the human apoE2 or apoE3 cDNAs, can express and secrete human apoE.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…29,[31][32][33][34][35] We have examined the feasibility of targeting muscle as a platform for the secretion of anti-atherogenic proteins by the transfection of mouse myoblast cultures with rAAV-based plasmid vectors containing apoA1 and LCAT cDNAs. 42 A significant improvement in secretion of apoA1 and LCAT and retention of vector sequences by transfected cells was observed using the rAAV-based vectors compared with conventional plasmid expression vectors. We also demonstrated that cultured mouse C2C12 cells transfected with a plasmid expression vector containing the CMV promoter driving expression of the human apoE2 or apoE3 cDNAs, can express and secrete human apoE.…”
Section: Discussionmentioning
confidence: 97%
“…The rAAV plasmid vectors were constructed using pNTC3-CMV␤, 23,42 which contains the 5'-and 3'-ITRs between which is a CMV promoter/LacZ expression cassette. The LacZ gene was deleted from pNTC3-CMV␤ by NotI and EcoRV digestion, and replaced with the human apoE2 and apoE3 cDNAs excised from their respective pUC-based vectors, 57 using HincII/SmaI digestion then blunt-ended, producing the rAAV plasmid vectors pAAV/apoE2 and pAAV/apoE3.…”
Section: Materials and Methods Raav Vector Constructionmentioning
confidence: 99%
“…In vivo LCAT gene transfer to apoAI transgenic mice show an increase in HDL production [27]. This principle has been further developed in in vitro gene transfer studies using adenovirus with both apoAI and LCAT genes [28]. Another possibility to treat dyslipemias is to use lipid transfer protein overexpression in vivo [29].…”
Section: Lecithin Cholesterol Acyltransferase and Lipid Transfer Protmentioning
confidence: 97%
“…Only a few published studies make use of an AAVderived vector to coexpress genes of interest, probably due to the transgene size limitation. Successful examples include the coexpression of anti-atherogenic ApoAI with lecithine acetyltransferase 34 or the prevention of tumor progression in experimental gliomas after thymidine kinase and interleukin-2 coexpression. 35 In both studies, the EMCV IRES was used.…”
Section: Aav-derived Bicistronic Vector With the Fgf-1 Ires A Delluc-mentioning
confidence: 99%